Sufi Healing dalam Tarekat Alawiyah dan Perspektif Tasawuf Al-Ghazali: A Comparative Study from Al-Ghazali’s Sufism and Psychological Perspective - Khomsin, Hanif Silmi; Nuha, Moch. Syihabudin; Santoso, Agus (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Happiness is the goal of life that everyone desires. Happy people can be careful in their decision-making, actions, and efforts to achieve happiness itself. Tarekat is a spiritual organization with specific methods as a form of practicing Sufism teachings that have a healing dimension. The Sufi healing dimension in this tarekat focuses on healing the soul so that Sufi practitioners can improve their mental well-being through the teachings of zuhud, tawakal, khauf, and mahabbah. The purpose of this study is to examine the dimension of Sufi healing in the teachings of the Alawiyah Order based on Al-Ghazali's Sufi perspective. This study uses a literature review approach by collecting various literature through searches based on relevant discussions in research, ranging from books to articles; literature processing; filtering; combining and drawing relevant conclusions. This research shows that conceptually produces a psychological concept that connects the basic principles of the teachings of the Alawiyah Tarekat and the framework of Al-Ghazali's Sufism with the path of Sufi healing in the modern era. Modern psychological and scientific concepts that have been developed include preventing distorted thinking that causes stress, righteous deeds driven by increased productivity and happiness, motivation for self-improvement and repentance, generating positive energy, and being able to make wise decisions through self-awareness.